Kinematic and Kinetic Waveform Changes of the Knee Joint Following a Mobile Bearing Total Knee Arthroplasty-Gait Analysis and Single Step Ascent. - Apostolopoulos, A P; E Chronopoulos; Michos, I V; Mastrokalos, D; Darras, N; Nikolaou, V S (J Knee Surg, 2019)
The objective of this study is to analyze the kinetic and kinematic changes of the osteoarthritic knee after a mobile bearing total knee arthroplasty. Kinematic and kinetic gait analysis of level walking was performed in 15 patients (eight female and seven male) with knee ostoarthritis. All patients were free of any neurological diseases that could affect their normal gait. Mean age was 68.6 ± 5.2 years, mean height 159.8 ± 6.9 cm, and mean weight was 78.5 ± 10.1 kg. Full body gait analysis was performed using the BioKin three-dimensional (3D) motion analysis system preoperatively and 9 months after total knee arthroplasty. A single-step ascending kinetic analysis and a plantar pressure distribution analysis were also performed in all patients. An increased average cadence (mean 99.39 step/min preoperatively and 104.64 step/min postoperatively;  = 0.152), step length (0.44 m preoperatively and 0.52 m postoperatively;  < 0.001), stride length (0.89 m preoperatively and 1.0 m postoperatively;  < 0.007), and walking velocity (0.73 m/sec preoperatively and 0.90 m/sec postoperatively;  = 0.005) were noted postoperatively and postoperatively. A decrease in the stance duration percentage and the knee adduction moment was also reported postoperatively. All patients showed a significant improvement of knee kinetics and kinematics after a mobile bearing total knee arthroplasty. Statistically significant differences were found in the step length, stride length, and walk velocity postoperatively. The knee adduction moment was also significantly reduced. Further research is warranted to determine the clinical relevance of these findings. This study is a prospective comparative one and reflects level II evidence.